‘Un-thirsty’ hypernatremia - Markus Koster; Katrin Ledergerber; Michael Brändle (Endocrinology, Diabetes & Metabolism Case Reports, 2025)
A 38-year-old man was admitted because of transient somnolence. Five weeks previously, he had suffered a subarachnoid hemorrhage from a ruptured aneurysm of the anterior communicating artery (ACOM), which was treated by craniotomy and clipping. He had recovered well, although loss of short-term memory and a forehead paresis on the side of craniotomy persisted. Clinical examination on admission showed no new neurological deficits. Cerebral computed tomography with angiography revealed no bleeding or infarction and correctly positioned clips. Laboratory examination showed severe hypernatremia (179 mmol/L). The patient was admitted to the intensive care unit (ICU) and treated with oral fluids and 5% glucose intravenously. Remarkably, he denied being thirsty and had to be encouraged to drink. Urine osmolality quickly fell to 294 mOsm/kg, polyuria of up to 400 mL/h was measured, and serum sodium remained elevated. Therefore, diabetes insipidus (DI) was obvious. After application of desmopressin acetate, urine output dropped to around 50 mL/h, confirming central DI or vasopressin deficiency (VD). Desmopressin acetate dose and volume management were continuously adjusted to blood sodium to restore euvolemia. Drinking volume needed to be supervised because of persistent lack of thirst and amnesia of being told to drink. Adipsic VD (aAVP-D) is a rare syndrome characterized by the combination of VD and loss of thirst in response to hypernatremia. It usually occurs within days after cell damage of osmoreceptors, for example after disruption of blood supply as in clipping of an ACOM aneurysm. Management includes titrated desmopressin acetate replacement, fixed water intake, weight monitoring, patient education and sodium monitoring.